Scaling Up Community Action for Tackling Climate Change. (15th April 2018) - Shaw, Deirdre; Cumbers, Andrew; McMaster, Robert; Crossan, John
Abstract: Tackling climate change requires a set of deeply intertwined geographical responsibilities whereby actors at and across different geographical scales are intimately connected. Creating effective strategies requires far more than an invocation for individual behavioural change in thinking globally and acting locally, but attention to the multi‐scalar conflicts, tensions and also opportunities to develop the most appropriate collective responses. In this paper, we use the example of community gardening initiatives in a large UK city to critically interrogate the problems facing groups at the local neighbourhood level in pursuing sustainability agendas. We focus on the organizational imperative to create a multi‐scalar food policy partnership at the city level as a way of confronting dominant global neoliberal urban competitiveness agendas. Our results emphasize the critical importance of scalar politics in enabling effective climate change strategies.